Assessment of the effect of ozonated water irrigation on gingival inflammation in patients undergoing fixed orthodontic treatment - Priya Jose; Biniraj Kannanganatt Ramabhadran; Rishi Emmatty; Tony Pallipurathukaran Paul (Wolters Kluwer Medknow Publications, 2017)
Background: A split-mouth longitudinal study was designed here to evaluate the effect of ozonated water delivered subgingivally through a jet device (Kent Ozone dental TY 820 jet) in controlling gingival inflammation of patients undergoing fixed orthodontic therapy. Materials and Methods: Twenty-eight patients undergoing fixed orthodontic treatment following thorough oral prophylaxis were recalled after 2 weeks, and baseline gingival inflammation was estimated. This study was conducted as split-mouth technique with the upper left quadrant (Control side) was irrigated by jetting saline into sulcus by air-water syringe with gauge 22 needle tip and upper right quadrant (Test side) irrigated with ozonated water by a jet device using similar delivery tip. The patients were recalled at the end of 1st, 2nd, 3rd, and 4th month and the irrigations as well as gingival inflammation estimation were repeated. A biochemical assessment of gingival inflammation (estimation of aspartate aminotransferase [AST] in gingival crevicular fluid [GCF]) and clinical assessment (gingival index scoring) was done at each visit. Results: At the test side, the AST level in the GCF was found to be maintained almost the same value as baseline till the end of 4th month, indicating not much of change in inflammatory status. Statistically significant difference in GCF-AST and gingival index score between test and control sites were found at the end of 3rd and 4th month with a significance of P < 0.05. Conclusion: The patient undergoing fixed orthodontic treatment showed a consistent improvement in gingival inflammation on frequent irrigation with ozone jet irrigation as compared with saline irrigation delivered with same jetting force.